2022
DOI: 10.1037/pspi0000291
|View full text |Cite
|
Sign up to set email alerts
|

Victims need more than power: Empowerment and moral change independently predict victims’ satisfaction and willingness to reconcile.

Abstract: Punishing offenders for their misdeeds can restore a sense of justice achieved (i.e., justice-related satisfaction) among victims and increase their willingness to reconcile, especially if offenders signal that they understand why punishment has been inflicted on them. In this article, we theoretically disentangle and empirically test two explanations for this effect. One possible interpretation for this effect is that offender feedback empowers the victim and that empowerment is the crucial prerequisite for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…The current findings again support the idea that the restoration of victims' sense of power as well as the re-affirmation of values are two separate ways contributing to justice perceptions (Wenzel et al, 2008) and specifically victims' justice-related satisfaction (see also Fischer et al, 2022).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The current findings again support the idea that the restoration of victims' sense of power as well as the re-affirmation of values are two separate ways contributing to justice perceptions (Wenzel et al, 2008) and specifically victims' justice-related satisfaction (see also Fischer et al, 2022).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, others have found that restorative responses to offences can increase justice perceptions without harmful punishment (Braithwaite, 1998;Wenzel & Okimoto, 2014). These findings suggest that the positive effects of offender change on victims' justice-related satisfaction are broader than originally suggested (Fischer et al, 2022;Funk et al, 2014) and do not only refer to instances of punishment. Thus, the current studies showed that offender change had beneficial effects even in the absence of punishment.…”
Section: Offender Change Increases Justice-related Satisfactionmentioning
confidence: 84%
See 2 more Smart Citations
“…Importantly, this does not mean that people consider punishment to be fair only to the extent that it makes the offender suffer (the proverbial eye-for-an-eye principle; the “lex talionis”). Rather, the findings reported here and elsewhere (e.g., Fischer et al, in press; Funk et al., 2014) suggest that punishment helps close the injustice gap (in the eyes of the punisher) even in the absence of suffering on the part of the offender (Aharoni et al., 2022). Thus, rebalancing the scales of justice can be achieved in many different ways.…”
Section: Discussionmentioning
confidence: 45%